Data from: New small-bodied ornithopods (Dinosauria, Neornithischia) from the Early Cretaceous Wonthaggi Formation (Strzelecki Group) of the Australian-Antarctic rift system, with revision of Qantassaurus intrepidus Rich and Vickers-Rich, 1999 ... - Herne, Matthew C.; Nair, Jay P.; Evans, Alistair R.; Tait, Alan M. (Dryad, 2019)
The Flat Rocks locality in the Wonthaggi Formation (Strzelecki Group) of the Gippsland Basin, southeastern Australia, hosts fossils of a late Barremian vertebrate fauna that inhabited the ancient rift between Australia and Antarctica. Known from its dentary, Qantassaurus intrepidus Rich and Vickers-Rich, 1999 has been the only dinosaur named from this locality. However, the plethora of vertebrate fossils collected from Flat Rocks suggests that further dinosaurs await discovery. From this locality, we name a new small-bodied ornithopod, Galleonosaurus dorisae n. gen. n. sp. from craniodental remains. Five ornithopodan genera are now named from Victoria. Galleonosaurus dorisae n. gen. n. sp. is known from five maxillae, from which the first description of jaw growth in an Australian dinosaur is provided. The holotype of Galleonosaurus dorisae n. gen. n. sp. is the most complete dinosaur maxilla known from Victoria. Micro-CT imagery of the holotype reveals the complex internal anatomy of the neurovascular tract ... : NMVP229196-tiffs-6-199MicroCT tiff series, holotypic maxilla (NMV P229196) of Galleonosaurus dorisae (part 1); Zeiss Xradia XRM Versa520 X-Ray Microtomography: voxel size 45.61 µm; power 10 W; voltage 140 kVNMV P229196-tiffs-202-499MicroCT tiff series, holotypic maxilla (NMV P229196) of Galleonosaurus dorisae (Part 2); Zeiss Xradia XRM Versa520 X-Ray Microtomography: voxel size 45.61 µm; power 10 W; voltage 140 kVNMVP229196-tiffs-503-899MicroCT tiff series, holotypic maxilla (NMV P229196) of Galleonosaurus dorisae (part 3); Zeiss Xradia XRM Versa520 X-Ray Microtomography: voxel size 45.61 µm; power 10 W; voltage 140 kVNMVP229196-tiffs-901-1199MicroCT tiff series, holotypic maxilla (NMV P229196) of Galleonosaurus dorisae (part 4); Zeiss Xradia XRM Versa520 X-Ray Microtomography: voxel size 45.61 µm; power 10 W; voltage 140 kVNMV P229196-tiffs-1203-1499MicroCT tiff series, holotypic maxilla (NMV P229196) of Galleonosaurus dorisae (part 5); Zeiss Xradia XRM Versa520 X-Ray Microtomography: voxel size 45.61 µm; ...